TINGKAT PEMAHAMAN MALPRAKTIK MAHASISWA FAKULTAS KEDOKTERAN SEMESTER AKHIR ANGKATAN 2019 - Uyun, Andi Quratul; Nirmalasari, Nila; Husairi, Ahmad; Aflanie, Iwan; Panghiyangani, Roselina (Homeostasis, 2023)
Malpractice is not only limited to the health profession but can also occur in other professions. Medical malpractice can be committed by doctors, nurses, midwives or other health workers whose actions deviate from medical standards.The problem of malpractice in health services today is being interesting topic for many people among various groups. It is proved by the many malpractice cases handled by the Honorary Council of Indonesian Medical Discipline (MKDKI). One of the reasons lies on the lack of communication between doctors or medical personnel and patients. One of the purposes of this research is to measure the level of understanding of doctor candidates about malpractice so that it is easier to follow up on it. his research used observation research method by taking data from medical students 2019 who are in the final semester to determine the students’ level of malpractice understanding. The sample of this research were decided by using purposive sampling in non-probability sampling technique. The results showed that there are 8 students (13%) in the high level,47 students (78%) in moderate level and 5 students (8%) in deficient level of malpractice understanding in the final semester students of medicine faculty at University of Lambung Mangkurat.